How Do German SMEs Cope with the Increasing Need for Flexibility?. (6th September 2012) - Roitzsch, Katharina; Hacker, Winfried; Pietrzyk, Ulrike; Debitz, Uwe
Abstract : Within this study a qualitative approach was chosen to find out whether German SMEs deal with flexibility requirements rather strategically or intuitively. Results show that many SMEs do not show strategic approaches. Possible reasons are seen in lacking organizational resources as well as the limited training of the CEOs. A toolbox has been developed to offer applicable information about flexibility measures on a low level.